Characteristics of synchrotron radiation of storage ring nestor and its applications - Ivashchenko, V.E.; Karnaukhov, I.M.; Kovalyova, N.V.; Shcherbakov, A.A.; Zelinsky, A.Yu. (Вопросы атомной науки и техники, 2004)
The results of calculations of the basic SR characteristics, generated from bending magnets of the storage ring NESTOR are presented. The methods of parameter measurements of a circulating beam with SR are considered. The possible areas of SR application of the storage ring NESTOR are given. Проведено розрахунок основних характеристик СВ, що генерується з поворотних магнітів нагромаджувача електронів НЕСТОР. Розглянуто методики проведення вимірів параметрів циркулюючого пучка за допомогою СВ. Приведено можливі області застосування СВ нагромаджувача НЕСТОР. Проведен расчет основных характеристик СИ, генерируемого из поворотных магнитов накопителя электронов НЕСТОР. Рассмотрены методики проведения измерений параметров циркулирующего пучка с помощью СИ. Приведены возможные области применения СИ накопителя НЕСТОР.